Bowie : the Illustrated Story. - Gilbert, Pat (Voyageur Press, 2017)
Follow every step of David Bowie's career; from Ziggy Stardust to Tin Machine, from "Space Oddity" to Let's Dance to Blackstar, in Bowie: The Illustrated Story.